A night in terror tower - Stine, R. L. (New York : Scholastic, 1995)
While visiting London, twelve-year-old Sue and her younger brother, Eddie get separated from their tour group and find themselves all alone in a gloomy old prison tower where a strange dark figure wants them dead.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
4.0.
008-012.
510
Accelerated Reader AR
Keywords: Horror tales; Brothers and sisters -- Fiction; London (England) -- Fiction